Questioning the role of sparse coding in the brain. Issue 7 (July 2015) - Spanne, Anton; Jörntell, Henrik
Highlights: Sparse coding is questioned on both theoretical and experimental grounds. Generalization is important to current brain models but is weak under sparse coding. The beneficial properties ascribed to sparse coding can be achieved by alternative means. Abstract : Coding principles are central to understanding the organization of brain circuitry. Sparse coding offers several advantages, but a near-consensus has developed that it only has beneficial properties, and these are partially unique to sparse coding. We find that these advantages come at the cost of several trade-offs, with the lower capacity for generalization being especially problematic, and the value of sparse coding as a measure and its experimental support are both questionable. Furthermore, silent synapses and inhibitory interneurons can permit learning speed and memory capacity that was previously ascribed to sparse coding only. Combining these properties without exaggerated sparse coding improves the capacity for generalization and facilitates learning of models of a complex and high-dimensional reality.